2013
DOI: 10.1186/1824-7288-39-34
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and associations with climatic conditions of Mycoplasma pneumoniae and Chlamydophila pneumoniae infections among Chinese children hospitalized with acute respiratory infections

Abstract: BackgroundThe incidence of severe acute respiratory tract infections in children caused by Mycoplasma pneumoniae (syn. Schizoplasma pneumoniae) and Chlamydophila pneumoniae (formerly Chlamydia pneumoniae) varies greatly from year to year and place to place around the world. This study investigated the epidemiology of M. pneumoniae and C. pneumoniae infections among children hospitalized with acute respiratory infections in Suzhou, China in the year 2006, and associations between incidence rates and climatic co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
3
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 44 publications
(49 citation statements)
references
References 30 publications
4
41
3
1
Order By: Relevance
“…In investigations without controls, C. pneumoniae DNA was found in 5% to 26% of patients diagnosed with acute respiratory infections such as CAP or bronchitis [20,39,41,42]. Miyashita and colleagues found that 8% of patients with acute respiratory disease had DNA in their respiratory samples, compared with 3% of asymptomatic controls [40].…”
Section: Discussionmentioning
confidence: 99%
“…In investigations without controls, C. pneumoniae DNA was found in 5% to 26% of patients diagnosed with acute respiratory infections such as CAP or bronchitis [20,39,41,42]. Miyashita and colleagues found that 8% of patients with acute respiratory disease had DNA in their respiratory samples, compared with 3% of asymptomatic controls [40].…”
Section: Discussionmentioning
confidence: 99%
“…After completing a full clinical record, nasopharyngeal aspirate (NPA) was performed on each child enrolled as described previously [16] and stored at 4 °C until sent to the clinical laboratory for further direct immunofluorescence assay and polymerase chain reactions (PCR) analysis. Pending the molecular diagnostic, all samples were stored at −80 °C after DNA or RNA extraction.…”
Section: Methodsmentioning
confidence: 99%
“…In addition to the link with cardiovascular diseases, it has also been linked with asthma (49), Alzheimer's disease (50,51), arthritis (52), lung cancer (53-55), chronic obstructive pulmonary disease (56,57), and diabetes (58,59). While there continue to be individual reports of severe respiratory disease associated with C. pneumoniae (60), it appears that the norm is now an association of C. pneumoniae with a range of chronic diseases. In addition to its widespread prevalence in the human population, C. pneumoniae also causes infection and disease in a wide range of animals.…”
mentioning
confidence: 99%